Iron cycle synergistic nitrogen removal biological retention tank
Patent Information
- Application Number
- CN202510699406.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-28
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-05-28
AI Technical Summary
[0004]针对现有技术存在的上述不足,本发明的目的在于提供一种铁循环协同强化脱氮的生物滞留池,能够保障硝酸盐去除效率的同时实现淹没区DON的生物代谢,减少副产物的产生,延长填料使用寿命,以解决现有技术对硝酸盐以及DON去除效果不佳的问题
[0016] 1. In this invention, biochar is specially used as a filler in the flooding layer. The interfacial reaction between iron ions and biochar can enhance its adsorption of nitrates and organic carbon. At the same time, it can also provide binding sites for iron oxidation and reduction products, avoiding excessive precipitation of iron ions on the surface of microbial cells or discharge with water. The oxidation-reduction capacity of biochar itself can also participate in iron cycling and electron regulation.
Smart Images

Figure CN120349060B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of rainwater treatment technology, specifically to a biological retention pond for enhanced nitrogen removal through iron recycling. Background Technology
[0002] With the acceleration of urbanization, urban non-point source pollution is becoming increasingly prominent. Bioretention facilities are the most commonly used individual facilities in sponge city construction, and they have good removal effects on suspended solids (SS), heavy metals, and pathogens, but their removal efficiency for dissolved nitrogen and phosphorus is low. Nitrates and dissolved organic nitrogen (DON) are the key pollutants that limit the improvement of nitrogen removal efficiency of bioretention facilities.
[0003] Because both natural filter media and nitrates carry a negative charge, nitrates are difficult to remove by electrostatic adsorption. Simultaneously, the scarcity of readily degradable organic carbon sources in surface runoff limits nitrate removal through microbial denitrification. Current technologies have shown that adding a submerged zone at the bottom of a bioretention facility and supplementing it with solid organic carbon sources can significantly improve the denitrification rate and nitrate removal rate. However, since the carbon release rate of solid organic carbon sources varies with the total carbon content and operating time, the amount of carbon released by solid organic carbon sources cannot be accurately matched with the carbon source requirements of heterotrophic denitrification, leading to secondary pollution. On the other hand, achieving DON removal in the submerged zone remains a major research challenge. DON cannot be rapidly removed through ion exchange, and its biological metabolism is hindered by dissolved oxygen and microbial activity. DON's high hydrophilicity allows it to easily migrate to the submerged zone with the water, but this area lacks sufficient dissolved oxygen and relevant functional microbial communities, making DON biological metabolism difficult to achieve. Summary of the Invention
[0004] To address the aforementioned shortcomings of existing technologies, the present invention aims to provide a biological retention tank for enhanced denitrification through iron circulation, which can ensure nitrate removal efficiency while enabling biological metabolism of DON in the submerged zone, reducing the generation of byproducts, and extending the service life of the packing material, thereby solving the problem of poor nitrate and DON removal efficiency in existing technologies.
[0005] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:
[0006] A bioretention tank for enhanced denitrification through iron recycling includes a tank body. Within the tank body, vertically arranged from top to bottom, are a water storage layer, a gravel layer, an aerobic layer, an organic carbon source layer, a submerged layer, a quartz sand transition layer, and a pebble drainage layer. The submerged layer is filled with a mixture of quartz sand, biochar, and hematite. Simultaneously, denitrifying sludge, iron-reducing sludge, and Feammox sludge are inoculated into the submerged layer. A perforated water collection pipe is installed within the pebble drainage layer, with one end connected to the pebble drainage layer and the other end connected to the inlet of a raised effluent pipe. An overflow tank is also provided on one side of the tank body, with the outlet of the raised effluent pipe connected to the overflow tank, and the effluent from the overflow tank flowing into the municipal stormwater network. An overflow pipe is located at the top of the tank body, connected to the overflow tank.
[0007] Preferably, the gravel layer is filled with gravel with a particle size of 8mm to 12mm, wherein the thickness of the gravel layer is 50mm.
[0008] Preferably, the aerobic layer is composed of quartz sand and zeolite, and the thickness of the aerobic layer is 250-300 mm; wherein, calculated by volume percentage, quartz sand with a particle size of 1 mm-2 mm accounts for 30%-50%, zeolite with a particle size of 0.5 mm-1 mm accounts for 30%-50%, quartz sand with a particle size of 0.425 mm-0.85 mm accounts for 10%-20%, and quartz sand with a particle size of 0.125 mm-0.175 mm accounts for 4%-10%.
[0009] Preferably, the organic carbon source layer is composed of wood chips and quartz sand, and the thickness of the organic carbon source layer is 150-250 mm; wherein, calculated by volume percentage, wood chips with a particle size of 2 mm-6 mm account for 5%-15%, quartz sand with a particle size of 1 mm-2 mm accounts for 15%-25%, quartz sand with a particle size of 0.425 mm-0.85 mm accounts for 40%-50%, quartz sand with a particle size of 0.175 mm-0.425 mm accounts for 5%-15%, and quartz sand with a particle size of 0.125 mm-0.175 mm accounts for 10%-20%.
[0010] Preferably, the submerged layer is composed of coconut shell biochar, quartz sand, and hematite, with a thickness of 250–350 mm. Specifically, by volume percentage, the coconut shell biochar with a particle size of 0.85 mm–1.70 mm comprises 5%–15%, the quartz sand with a particle size of 1 mm–2 mm comprises 20%–30%, the quartz sand with a particle size of 0.425 mm–0.85 mm comprises 40%–50%, the quartz sand with a particle size of 0.175 mm–0.425 mm comprises 5%–10%, and the quartz sand with a particle size of 0.125 mm–0.175 mm comprises 10%–15%. Hematite and Feammox sludge are uniformly mixed and spread in a layer every 5 cm in the submerged layer. Iron-reducing sludge (mainly containing iron-reducing bacteria) and denitrifying sludge (mainly containing denitrifying bacteria) are inoculated on the top layer of the submerged layer.
[0011] Preferably, the quartz sand transition layer is composed of quartz sand with different particle sizes, and the thickness of the quartz sand transition layer is 50 mm; wherein, calculated by volume percentage, quartz sand with a particle size of 1 mm to 2 mm accounts for 25% to 35%, quartz sand with a particle size of 0.425 mm to 0.85 mm accounts for 35% to 45%, quartz sand with a particle size of 0.175 mm to 0.425 mm accounts for 5% to 15%, and quartz sand with a particle size of 0.125 mm to 0.175 mm accounts for 15% to 25%.
[0012] Preferably, the pebble drainage layer is filled with pebbles with a particle size of 6mm to 9mm and a pebble drainage layer thickness of 100mm.
[0013] Preferably, the outlet end of the raised water pipe is raised to half the thickness of the organic carbon source layer and level with it.
[0014] Preferably, the permeability coefficient of the aerobic layer is 400-600 mm / h; the permeability coefficient of the organic carbon source layer is 300-500 mm / h; the permeability coefficient of the submerged layer is 300-500 mm / h; and the permeability coefficient of the quartz sand transition layer is not less than 250 mm / h.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] 1. In this invention, biochar is specially used as a filler in the flooding layer. The interfacial reaction between iron ions and biochar can enhance its adsorption of nitrates and organic carbon. At the same time, it can also provide binding sites for iron oxidation and reduction products, avoiding excessive precipitation of iron ions on the surface of microbial cells or discharge with water. The oxidation-reduction capacity of biochar itself can also participate in iron cycling and electron regulation.
[0017] 2. This invention utilizes sawdust from the organic carbon source layer to promote the removal of nitrates through heterotrophic denitrification; simultaneously, the ammonia nitrogen produced by DON deammoniation can react with hematite and be converted into N2 and Fe(II) via the Feammox pathway, while NO in the influent... x - It can also be converted into nitrogen and Fe(III) through iron autotrophic denitrification with the generated Fe(II), thus realizing the iron cycle.
[0018] 3. This invention utilizes the interaction between biochar and microorganisms. Biochar, as an electron carrier, can promote the utilization of iron by microorganisms and the heterotrophic denitrification of nitrogen by using adsorbed organic carbon. At the same time, the rich pore structure inside biochar can not only increase the biomass of active microorganisms, but also form different ecological niches to increase microbial diversity and promote iron cycling and denitrification processes.
[0019] 4. This invention discovers that, compared to traditional layered structures where the permeability coefficient is prone to a sharp drop due to the migration of fine particles, this invention stabilizes the permeability coefficient of each layer at 300-500 mm / h by controlling the particle size gradient of the quartz sand transition layer (0.125-2 mm) and the skeletal support of the biochar in the submerged layer. This is an improvement over conventional systems and can effectively avoid the risk of waterlogging. Attached Figure Description
[0020] Figure 1 This is a schematic diagram of the structure of the biological retention tank for iron recycling and synergistic denitrification as described in this invention.
[0021] In the diagram: 1. Pool body; 2. Water storage layer; 3. Gravel layer; 4. Aerobic layer; 5. Organic carbon source layer; 6. Submerged layer; 7. Quartz sand transition layer; 8. Pebble drainage layer; 9. Perforated water collection pipe; 10. Elevated water outlet pipe; 11. Overflow pool; 12. Rainwater pipe network; 13. Overflow pipe. Detailed Implementation
[0022] The technical solutions of the present invention will be clearly and completely described in conjunction with the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the present invention are within the scope of protection of the present invention.
[0023] Unless otherwise specified in the specific circumstances, the numerical ranges listed herein include upper and lower limits, as well as all integers and fractions within that range, but are not limited to the specific values listed when the range is defined.
[0024] I. A biological retention tank for enhanced nitrogen removal through iron recycling
[0025] The bioretention tank of this invention includes a tank body. Within the tank body, vertically arranged from top to bottom, are a water storage layer, a gravel layer, an aerobic layer, an organic carbon source layer, a submerged layer, a quartz sand transition layer, and a pebble drainage layer. The aerobic layer is filled with a graded mixture of quartz sand and zeolite; the organic carbon source layer is filled with a graded mixture of quartz sand and wood chips; and the submerged layer is filled with a graded mixture of quartz sand, biochar, and hematite. Simultaneously, denitrifying sludge, iron-reducing sludge, and Feammox sludge are inoculated into the submerged layer. A perforated water collection pipe is installed within the pebble drainage layer, with one end connected to the pebble drainage layer and the other end connected to the inlet of a raised outlet pipe. An overflow tank is also provided on one side of the tank body, with the outlet of the raised outlet pipe connected to the overflow tank, and the overflow water flows into the municipal stormwater network. An overflow pipe is located at the top of the tank body, connected to the overflow tank.
[0026] This invention, after in-depth research into traditional bioretention systems, reveals several key issues. First, traditional bioretention systems primarily rely on carbon-driven heterotrophic denitrification, resulting in poor nitrogen removal efficiency at low C / N ratios. To address this, this invention proposes a multi-pathway synergistic nitrogen removal mechanism combining iron redox cycles, Feammox, and iron autotrophic denitrification to improve nitrogen removal efficiency under low C / N ratio conditions. Second, traditional bioretention systems mainly utilize iron materials as electron donors or for co-precipitation phosphorus removal, leading to easy iron ion loss or passivation. Therefore, this invention proposes using biochar to stabilize the nitrogen removal process and promote the circulation of iron redox within the bioretention tank's submerged area, thereby improving nitrogen removal efficiency and long-term stability. Third, traditional bioretention systems are dominated by heterotrophic denitrifying bacteria, resulting in a relatively homogeneous microbial population. DON (dioxanone) migrating with the water to the submerged area is difficult to degrade through microorganisms. Therefore, this invention employs a composite microbial system, including heterotrophic denitrifying bacteria, iron-reducing bacteria, Feammox bacteria, and sulfur-reducing bacteria, to form a highly efficient and sustainable nitrogen removal system. Finally, traditional bioretention systems are prone to clogging of the packing material, resulting in uneven water flow distribution and short-circuiting. This invention optimizes hydraulic characteristics by employing a reasonable particle size distribution of the packing material to improve permeability, prevent clogging, and increase hydraulic retention time. The denitrifying sludge, iron-reducing sludge, and Feammox sludge all originate from activated sludge in wastewater treatment plants. This activated sludge contains a relatively rich variety of heterotrophic denitrifying bacteria; however, it is a mixture, containing a diverse array of microorganisms, with relatively low abundances of autotrophic denitrifying bacteria and Feammox functional bacteria. To increase the abundance of functional bacteria with specific functions among these mixed bacteria, enrichment culture of the activated sludge is necessary. The standard for successful enrichment culture is that the enriched sludge achieves a removal efficiency of over 90% for a particular type of pollutant in the influent. For example, denitrifying sludge is produced from wastewater treatment plant sludge. By adding a substrate primarily composed of thiosulfate and nitrate, sulfur-autotrophic denitrifying bacteria in the sludge are enriched, thereby increasing the abundance of autotrophic denitrifying bacteria in the sludge. After enrichment and cultivation, it is used as denitrifying sludge. Feammox sludge also originates from wastewater treatment plant sludge. By adding a substrate primarily composed of hematite and ammonium chloride, Feammox bacteria and iron-autotrophic denitrifying bacteria are enriched, resulting in Feammox sludge. Iron-reducing sludge also originates from wastewater treatment plant sludge. By adding a substrate primarily composed of sodium pyruvate, sulfate, and ferric chloride, sulfur- and iron-reducing bacteria are enriched, resulting in iron-reducing sludge. Inoculating various types of acclimatized sludge into a bioretention tank can increase the abundance of functional bacteria in the bioretention tank, enabling them to survive in this environment and synergistically denitrify.
[0027] Based on this, the present invention employs a graded mixed filling method for the aerobic layer, organic carbon source layer, and submerged layer. Specifically, it uses fillers of different particle sizes for mixed filling, with particular emphasis on strict control over the formulation of the rainwater runoff treatment substrate; otherwise, various problems may arise. Uneven proportions may lead to facility collapse or particle leakage; excessively fine particle sizes will reduce hydraulic performance and increase the risk of clogging; while excessively coarse particle sizes may weaken pollutant removal capacity, reduce water retention, and disrupt the anoxic environment of the submerged area. Therefore, a reasonable proportion is crucial for ensuring substrate stability, permeability, and pollutant removal effectiveness. Figure 1 As shown, the bioretention tank of this invention includes a tank body, which, from top to bottom, comprises a water storage layer, a gravel layer, an aerobic layer, an organic carbon source layer, a submerged layer, a quartz sand transition layer, and a pebble drainage layer. A perforated water collection pipe is installed within the pebble drainage layer, and this perforated water collection pipe is connected to a raised outlet pipe. The outlet end of the raised outlet pipe is raised to half the thickness of the organic carbon source layer and flush with it. An overflow pipe is provided at the top opening of the tank body. A guide slope is provided along the edge of the tank body opening.
[0028] During the long-term operation of the retention tank described in this invention, when the treatment effect of the rainwater biological retention tank declines, maintenance can be achieved simply by renovating the aerobic layer substrate and the organic carbon source layer substrate.
[0029] Assuming the ratio of the surface area of the bioretention tank to the catchment area described in this invention is 1:20, and the comprehensive runoff coefficient is taken as 0.7, when this invention is used to handle low-intensity rainfall (defined as rainfall not exceeding 14.9 mm within 12 hours), the water flow velocity is suitable and the retention time is relatively long, which is conducive to sufficient contact between pollutants and the packing material. The gravel layer plays a role in uniform water distribution, provides good infiltration channels, and prevents short-circuiting. The aerobic layer, composed of appropriately graded quartz sand and zeolite, preferentially removes suspended particles, ammonia nitrogen, dissolved phosphorus, and other pollutants, while nitrification occurs during rainfall intervals, i.e., microorganisms convert adsorbed ammonia nitrogen into nitrate nitrogen under aerobic conditions. The organic carbon source layer, through the combination of quartz sand and sawdust, further removes some particulate pollutants and provides an organic carbon source to promote the metabolism of heterotrophic denitrifying bacteria and iron and sulfur-reducing bacteria. The synergistic effect of hematite (Fe2O3) and Feammox bacteria within the submerged layer further enhances the removal of DON and its denitrification products. Simultaneously, the synergistic effect of sulfur-autotrophic and iron-autotrophic denitrifying bacteria further improves denitrification efficiency, reducing the risk of eutrophication. A quartz sand transition layer protects the submerged packing material and prevents leakage. A pebble drainage layer diverts treated rainwater, preventing water stagnation. During heavy rainfall or even torrential downpours, the treatment capacity of the bioretention pond is significantly tested. The water storage layer ensures that the bioretention pond can absorb and retain some rainwater in a short time, reducing peak surface runoff and mitigating flood risk. The rationally graded quartz sand in each layer ensures high permeability while providing gradient filtration of pollutants. Materials such as coconut shell biochar enhance the adsorption capacity for organic pollutants, effectively purifying rainwater even under short-term high-flow conditions. When rainfall intensity exceeds the infiltration and storage capacity of the retention pond, some rainwater may be discharged from the overflow outlet. However, because initial pollutants have been reduced, the pollution of downstream water bodies by the discharged water is relatively low.
[0030] In some embodiments of the present invention, the gravel layer is made of gravel with a particle size of 8mm to 12mm, and the thickness of the gravel layer is 50mm. In the present invention, the thickness is the same as the height of the gravel layer, and other treatment layers are laid in the same manner.
[0031] In some embodiments of the present invention, the aerobic layer is composed of quartz sand and zeolite, and the thickness of the aerobic layer is 250-300 mm; wherein, calculated by volume percentage, the volume percentage of quartz sand with a particle size of 1 mm to 2 mm can be 30%, 35%, 40%, 45%, 50%, etc., and all ranges and sub-ranges between the above values; the volume percentage of zeolite with a particle size of 0.5 mm to 1 mm can be 30%, 35%, 40%, 45%, 50%, etc., and all ranges and sub-ranges between the above values; the particle size 0. The volume percentage of quartz sand with a particle size of 425mm to 0.85mm can be 10%, 15%, 20%, etc., as well as all ranges and sub-ranges between the above values; the volume percentage of quartz sand with a particle size of 0.125mm to 0.175mm can be 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., as well as all ranges and sub-ranges between the above values; it should be understood that, in the implementation scheme, any of the above ranges can be combined with any other ranges to ensure that the sum of the volume percentages of quartz sand and zeolite of different particle sizes is 100%.
[0032] In some embodiments of the present invention, the organic carbon source layer is composed of wood chips and quartz sand, and the thickness of the organic carbon source layer is 150-250 mm; wherein, calculated by volume percentage, the volume percentage of wood chips with a particle size of 2 mm-6 mm can be 5%, 10%, 15%, etc., and all ranges and sub-ranges between the above values; the volume percentage of quartz sand with a particle size of 1 mm-2 mm can be 15%, 20%, 25%, etc., and all ranges and sub-ranges between the above values; the volume percentage of quartz sand with a particle size of 0.425 mm-0.85 mm can be 40%, 45%, 5%, etc. The volume percentage of quartz sand with a particle size of 0.175 mm to 0.425 mm can be 5%, 10%, 15%, etc., and all ranges and sub-ranges between the above values; the volume percentage of quartz sand with a particle size of 0.125 mm to 0.175 mm can be 10%, 15%, 20%, etc., and all ranges and sub-ranges between the above values; it should be understood that, in the implementation scheme, any of the above ranges can be combined with any other ranges to ensure that the sum of the volume percentages of quartz sand with different particle sizes and wood chips is 100%.
[0033] In some embodiments of the present invention, the submerged layer is composed of coconut shell biochar, quartz sand, and hematite, and the thickness of the submerged layer is 250–350 mm. Specifically, the volume percentage of coconut shell biochar with a particle size of 0.85 mm–1.70 mm can be 5%, 10%, 15%, etc., and all ranges and sub-ranges between these values; the volume percentage of quartz sand with a particle size of 1 mm–2 mm can be 20%, 25%, 30%, etc., and all ranges and sub-ranges between these values; the volume percentage of quartz sand with a particle size of 0.425 mm–0.85 mm can be 40%, 45%, 50%. The values are defined as follows: The volume percentage of quartz sand with a particle size of 0.175 mm to 0.425 mm can be 5%, 6%, 7%, 8%, 9%, 10%, etc., and the volume percentage of quartz sand with a particle size of 0.125 mm to 0.175 mm can be 10%, 11%, 12%, 13%, 14%, 15%, etc., and the volume percentage of quartz sand with a particle size of 0.125 mm to 0.175 mm can be 10%, 11%, 12%, 13%, 14%, 15%, etc., and the volume percentage of quartz sand with a particle size of 0.125 mm to 0.175 mm. Hematite and Feammox sludge are uniformly mixed and then spread in a layer every 5 cm in the flooded layer. Iron-reducing bacteria and denitrifying bacteria are inoculated on the top layer of the flooded layer. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other ranges to ensure that the sum of the volume percentages of coconut shell biochar, quartz sand, and hematite with different particle sizes is 100%.
[0034] In some embodiments of the present invention, the quartz sand transition layer is composed of quartz sand of different particle sizes, and the thickness of the quartz sand transition layer is 50 mm; wherein, calculated by volume percentage, the volume percentage of quartz sand with a particle size of 1 mm to 2 mm can be 25%, 30%, 35%, etc., and all ranges and sub-ranges between the above values; the volume percentage of quartz sand with a particle size of 0.425 mm to 0.85 mm can be 35%, 40%, 45%, etc., and all ranges and sub-ranges between the above values; particle size The volume percentage of quartz sand with a particle size of 0.175mm to 0.425mm can be 5%, 10%, 15%, etc., as well as all ranges and sub-ranges between the above values; the volume percentage of quartz sand with a particle size of 0.125mm to 0.175mm can be 15%, 20%, 25%, etc., as well as all ranges and sub-ranges between the above values; it should be understood that, in the implementation scheme, any of the above ranges can be combined with any other ranges to ensure that the sum of the volume percentages of quartz sand with different particle sizes is 100%.
[0035] In some embodiments of the present invention, the pebble drainage layer is filled with pebbles with a particle size of 6mm to 9mm and a pebble drainage layer thickness of 100mm.
[0036] In some embodiments of the present invention, the permeability coefficient of the aerobic layer is 400-600 mm / h; the permeability coefficient of the organic carbon source layer is 300-500 mm / h; the permeability coefficient of the submerged layer is 300-500 mm / h; and the permeability coefficient of the quartz sand transition layer is not less than 250 mm / h.
[0037] II. Examples and Comparative Examples
[0038] Example 1
[0039] The structure of the bioretention tank in this embodiment is as follows: Figure 1 As shown, where:
[0040] The gravel particles in the gravel layer have a diameter of 8-12 mm.
[0041] The aerobic layer is 250mm high and is composed of the following materials mixed in the following volume ratio: 40% quartz sand (1-2mm), 40% zeolite (0.5-1mm), 15% quartz sand (0.425-0.85mm), and 5% quartz sand (0.125-0.175mm).
[0042] The organic carbon source layer has a height of 150 mm and is composed of the following materials mixed in the following volume ratios: 10% wood chips (2-6 mm), 20% quartz sand (1-2 mm), 45% quartz sand (0.425-0.85 mm), 10% quartz sand (0.175-0.425 mm), and 15% quartz sand (0.125-0.175 mm).
[0043] The submerged layer, with a height of 250 mm, is composed of the following materials mixed in the following volume ratios: 10% coconut shell biochar (0.85-1.70 mm), 25% quartz sand (1-2 mm), 45% quartz sand (0.425-0.85 mm), 7% quartz sand (0.175-0.425 mm), and 13% quartz sand (0.125-0.175 mm). Hematite and Feammox bacteria are evenly mixed and spread in a 5 cm layer throughout the submerged layer; sulfur-reducing bacteria and denitrifying bacteria are mainly found in the top layer of the submerged layer.
[0044] The quartz sand transition layer is composed of the following materials mixed in the following volume ratios: 30% quartz sand (1-2mm), 40% quartz sand (0.425-0.85mm), 10% quartz sand (0.175-0.425mm), and 20% quartz sand (0.125-0.175mm).
[0045] The pebble drainage layer contains pebbles with a particle size of 6-9 mm.
[0046] The permeability coefficients of the bioretention tank in this implementation case were tested using a constant head permeameter, and the results were as follows: the permeability coefficient of the aerobic layer was 418-448 mm / h; the permeability coefficient of the organic carbon source layer was 344.4-347.2 mm / h; the permeability coefficient of the submerged layer was 333.9-349.7 mm / h; and the permeability coefficient of the quartz sand transition layer was 347.2-357 mm / h.
[0047] Comparative Example 1
[0048] An improvement was made based on Example 1, the difference being that: no organic carbon source layer was set in Comparative Example 1, and no denitrifying sludge, iron-reducing sludge, and Feammox sludge were inoculated in the flooded layer.
[0049] The specific structure of the bioretention tank in Comparative Example 1 is as follows:
[0050] The gravel particles in the gravel layer have a diameter of 8-12 mm.
[0051] The aerobic layer is 300mm high and is composed of the following materials mixed in the following volume ratios: 40% quartz sand (1-2mm), 40% zeolite (0.5-1mm), 15% quartz sand (0.425-0.85mm), and 5% quartz sand (0.125-0.175mm).
[0052] The submerged layer is 300 mm high and is composed of the following materials mixed in the following volume ratios: 35% quartz sand (1-2 mm), 45% quartz sand (0.425-0.85 mm), 7% quartz sand (0.175-0.425 mm), and 13% quartz sand (0.125-0.175 mm).
[0053] The quartz sand transition layer is composed of the following materials mixed in the following volume ratios: 30% quartz sand (1-2mm), 40% quartz sand (0.425-0.85mm), 10% quartz sand (0.175-0.425mm), and 20% quartz sand (0.125-0.175mm).
[0054] The pebble drainage layer contains pebbles with a particle size of 6-9 mm.
[0055] The above are the differences between Comparative Example 1 and Example 1; the other structures are exactly the same as in Example 1.
[0056] Comparative Example 2
[0057] This is an improvement on Example 1, the difference being that an organic carbon source layer is not included. The structure of the bioretention tank in Comparative Example 2 is as follows: arranged vertically from top to bottom as follows:
[0058] The gravel particles in the gravel layer have a diameter of 8-12 mm.
[0059] The aerobic layer is 300mm high and is composed of the following materials mixed in the following volume ratios: 40% quartz sand (1-2mm), 40% zeolite (0.5-1mm), 15% quartz sand (0.425-0.85mm), and 5% quartz sand (0.125-0.175mm).
[0060] The submerged layer, 300 mm high, is composed of the following materials mixed in the following volume ratios: 10% coconut shell biochar (0.85-1.70 mm), 25% quartz sand (1-2 mm), 45% quartz sand (0.425-0.85 mm), 7% quartz sand (0.175-0.425 mm), and 13% quartz sand (0.125-0.175 mm). Hematite and Feammox bacteria are evenly mixed and spread in a 5 cm layer throughout the submerged layer. Sulfur-reducing bacteria and denitrifying bacteria are mainly found in the top layer of the submerged layer.
[0061] The quartz sand transition layer is composed of the following materials mixed in the following volume ratios: 30% quartz sand (1-2mm), 40% quartz sand (0.425-0.85mm), 10% quartz sand (0.175-0.425mm), and 20% quartz sand (0.125-0.175mm).
[0062] The pebble drainage layer contains pebbles with a particle size of 6-9 mm.
[0063] The above are the differences between Comparative Example 2 and Example 1; the other structures are exactly the same as in Example 1.
[0064] Example 1, Comparative Examples 1 and 2 were subjected to artificially prepared rainwater pollutant removal tests. Assuming a facility service area ratio of 1:20, a runoff coefficient of 0.7, a rainfall duration of 2 hours, and a rainfall amount of 12 mm, rainfall was simulated every three days, and the removal efficiency for total nitrogen was measured. The test results for total nitrogen removal are shown in Table 1.
[0065] Table 1. Average total nitrogen removal rate (%) in simulated runoff pollution.
[0066]
[0067] As shown in Table 1, this invention significantly improves the total nitrogen removal rate. Example 1: Overall stability indicates stable and reliable system operation; the removal rate remained high even after long-term operation following rain (e.g., 3.25 and 3.28), demonstrating the system's resistance to shock loads. Comparative Example 1: The removal rate remained around 60% without significant fluctuations, but lacked further improvement potential. Comparative Example 2: Initial results were similar to Example 1, but declined rapidly, indicating that the system's microbial or carbon source supply could not sustain a high nitrogen removal capacity. Therefore, the bioretention tank described in this invention, through multi-pathway synergistic nitrogen removal, optimizes the hydraulic structure, jointly improving nitrogen removal efficiency and system adaptability. It not only possesses advantages such as high efficiency, low energy consumption, anti-clogging, and long lifespan, but also has excellent prospects for widespread application.
[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit the technical solutions. Those skilled in the art should understand that any modifications or equivalent substitutions to the technical solutions of the present invention without departing from the spirit and scope of the present invention should be covered within the scope of the claims of the present invention.
Claims
1. A biological retention tank for enhanced nitrogen removal through iron recycling, characterized in that, The pool body (1) includes a water storage layer (2), a gravel layer (3), an aerobic layer (4), an organic carbon source layer (5), a flooding layer (6), a quartz sand transition layer (7), and a pebble drainage layer (8) arranged vertically from top to bottom. The process involves filling the submerged layer with a mixture of quartz sand, biochar, and hematite; simultaneously, the submerged layer is inoculated with denitrifying sludge, iron-reducing sludge, and Feammox sludge. The denitrifying sludge is enriched with sulfur-autotrophic denitrifying bacteria, the iron-reducing sludge is enriched with sulfur and iron-reducing bacteria, and the Feammox sludge is enriched with Feammox bacteria and iron-autotrophic denitrifying bacteria. A perforated water collection pipe (9) is installed inside the pebble drainage layer. One end of the perforated water collection pipe is connected to the pebble drainage layer, and the other end is connected to the inlet end of the raised outlet pipe (10). An overflow pool (11) is also provided on one side of the pool. The outlet end of the raised outlet pipe is connected to the overflow pool, and the water from the overflow pool flows into the municipal rainwater pipe network (12). An overflow pipe (13) is provided at the top of the pool. The overflow pipe is connected to the overflow pool. The organic carbon source layer has a thickness of 150-250 mm and is composed of wood chips and quartz sand; wherein, by volume percentage, wood chips with a particle size of 2 mm-6 mm account for 5%-15%, quartz sand with a particle size of 1 mm-2 mm accounts for 15%-25%, quartz sand with a particle size of 0.425 mm-0.85 mm accounts for 40%-50%, quartz sand with a particle size of 0.175 mm-0.425 mm accounts for 5%-15%, and quartz sand with a particle size of 0.125 mm-0.175 mm accounts for 10%-20%. The submerged layer has a thickness of 250-350 mm and is composed of coconut shell biochar, quartz sand, and hematite. Specifically, by volume percentage, the coconut shell biochar (0.85-1.70 mm particle size) accounts for 5%-15%, the quartz sand (1-2 mm particle size) for 20%-30%, the quartz sand (0.425-0.85 mm particle size) for 40%-50%, the quartz sand (0.175-0.425 mm particle size) for 5%-10%, and the quartz sand (0.125-0.175 mm particle size) for 10%-15%. Hematite and Feammox sludge are uniformly mixed and spread in a single layer every 5 cm in the submerged layer. Iron-reducing sludge and denitrifying sludge are inoculated onto the top layer of the submerged layer. Raise the outlet end of the water pipe to half the thickness of the organic carbon source layer and make it level with it.
2. The bioretention tank according to claim 1, characterized in that, The gravel layer is 50mm thick and contains gravel with a particle size of 8mm to 12mm.
3. The bioretention tank according to claim 1, characterized in that, The aerobic layer has a thickness of 250-300 mm and is composed of quartz sand and zeolite. Specifically, by volume percentage, quartz sand with a particle size of 1 mm-2 mm accounts for 30%-50%, zeolite with a particle size of 0.5 mm-1 mm accounts for 30%-50%, quartz sand with a particle size of 0.425 mm-0.85 mm accounts for 10%-20%, and quartz sand with a particle size of 0.125 mm-0.175 mm accounts for 4%-10%.
4. The bioretention tank according to claim 1, characterized in that, The quartz sand transition layer has a thickness of 50 mm and is composed of quartz sand of different particle sizes. Specifically, by volume percentage, quartz sand with a particle size of 1 mm to 2 mm accounts for 25% to 35%, quartz sand with a particle size of 0.425 mm to 0.85 mm accounts for 35% to 45%, quartz sand with a particle size of 0.175 mm to 0.425 mm accounts for 5% to 15%, and quartz sand with a particle size of 0.125 mm to 0.175 mm accounts for 15% to 25%.
5. The bioretention tank according to claim 1, characterized in that, The pebble drainage layer is 100mm thick, and the pebble particle size is 6mm~9mm.
6. The bioretention tank according to any one of claims 1 to 5, characterized in that, The permeability coefficient of the aerobic layer is 400~600 mm / h; the permeability coefficient of the organic carbon source layer is 300~500 mm / h; the permeability coefficient of the submerged layer is 300~500 mm / h; and the permeability coefficient of the quartz sand transition layer is not less than 250 mm / h.
Citation Information
Patent Citations
Two-way water inlet type rainwater bioretention pond
CN115010323A